Pengaruh Standar Operasional Prosedur dan Pengawasan Terhadap Kinerja Karyawan PT BPRS Amanah Ummah (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
Employee performance is certainly mani factors that suppot its success. An employee is said to be successful or failed if there are standards that measure his work and evaluation as a supervisory system set by the company. The purpose of the study was to determine the effect of standar operating procedures and supervision on the performance of employees of PT BPRS Amanah Ummah. Quantitative research method with explanatory approach, data collection by questionnaire as many as 30 respondents. The results of the study indicate that standar operating prosedures have a very high influence on employee performance. While the variable of supervision on employee performance has a high influence. Furthermore, the variables of standard operating prosedures and supervision together have an influence on the performance of employee of PT BPRS Amanah Ummah.